Representações do leitor infantil e juvenil em adaptações do clássico "Dom Quixote" para o público brasileiro - Oliveira, Jéssica de (2018)
The production, publication, and reading of adaptations of literary classics for children and youth, which has expanded since the twentieth century, is a practice whose indication is assumed by educational and other institutions, despite diverse criticisms of the value of some texts. The objective of this study is to analyze such adaptations of the universal classic Don Quixote de la Mancha as published in Brazil from 1910 to the 2013, through a literature review, to reflect on their depictions of their readers. To this end, its corpus comprised 13 adaptations selected in light of the following criteria: broad circulation, two or more editions, well-respected adaptors, and distinguished publishers, with even distribution across the study period. The study’s examination of one of the earliest Brazilian adaptations, published by Livaria Garnier, purportedly in 1915, informed its perspective on how depictions of the “mad knight errant” changed over time. The study compares adaptations with its primary source, Sérgio Molina's two-volume, bilingual edition (2007, 2008) as well as one adaption to another, in accordance with the principles of French discourse analysis, the cultural history of reading, and studies on adaptation of classical literature, and thus identifies madness as the most prominent feature in descriptions of the protagonist. The adaptations also reflect the concerns, anxieties, and demands of educational institutions at the time they were published, reflecting three tendencies: moralism; humor, in relation to madness; and an appreciation of the diversity of genres, forms, and paratexts in depicting Don Quixote. Analysis of the visibility accorded the author of the original classic and its adaptors indicate the latter are gaining prominence and even assuming authorship as evidenced by book covers, with the original author most ofen noted within.